Candidatus List No. 6 - Oren, Aharon; Kostovski, Marko; Göker, Markus (Microbiology Society, 2025)
Based on the guidelines of Appendix 11 of the International Code of Nomenclature of Prokaryotes (ICNP) [1, 2], a list in the form of a codified record of Candidatus organisms should be published at appropriate intervals in the International Journal of Systematic and Evolutionary Microbiology (IJSEM). In order to comply at least partially with the guidelines of Appendix 11, the List Editors have previously presented Candidatus List No. 1, which contained an inventory of the names of Candidatus taxa compiled from the literature published up to the end of 2018 [3]. Candidatus List No. 2, with names proposed in 2019 [4], was published in 2021, and Candidatus Lists No. 3 and 4, with names proposed in 2020 and 2021, respectively, were published in 2022 [5, 6]. The rank of phylum has recently been included [7] in the rules of the ICNP [1]. The first Candidatus Phylum List was published in 2023 [8].
Keywords: Candidatus; list; names